Model of Accumulation and Loss of Knowledge in Computerization Systems of Education with Remote Access - Omarov, M.; Muradova, V.; Lyashenko, V. (WARSE, 2020)
The article discusses the approach to the methods of creating expert assessments to determine the level of knowledge of students in education computerization systems with remote access. This is achieved through the use of the probabilistic approach and Bayesian processes in comparison with the approach based on the theory of fuzzy sets. A model for the accumulation and loss of knowledge is proposed. A life-cycle model of a student’s knowledge system has been developed. The model of finding the optimal periodicity of the learning process with forced interruptions is investigated.
Keywords: Fuzzy Sets; Bayesian Networks; Knowledge Life Cycle; Knowledge Base